حدیث" اطلبوا العلم ولو بالصین " کی اسنادی ومتنی حیثیت کا تحقیقی جائزہ : A research review of the authentic and textual status of the hadith "Get knowledge even if you have to go to China” - Yaqoob, Dr. Muhammad; Shahid, Dr. Muhammad (Acta-Islamica, 2023)
Hadith is the second permanent source of Islamic Shariah, from which Islamic laws are derived. The Hadith has two parts. One part is called “Sanad”, and the other part is called “ Matan”. These two parts of any Hadith must be verified. In this sense only those Ahadiths should be paid attention for research which are other than Sihaah e Sittah. And these Ahadith have either not been investigated thoroughly, or those have not been researched yet. It is not correct to narrate a hadith without this said research, otherwise it can be equivalent to tell a lie. At present, there are some Ahadiths whose “Sanad” and “Matan” are both daeef, but those are being presented as a part of religion without any hesitation. This article likewise explains the true nature of a Hadith that deals with the acquisition of knowledge, even if you have to go to China. It aslo discusses its origin and describes its form. It presents a full review of its “Sanad “and “Matan”. It also describes its unproven and proven parts of text separately.